Graves’ hyperthyroidism treated with potassium iodide: early response and after 2 years of follow-up - Megumi Fujikawa; Ken Okamura (European Thyroid Journal)
Objective: As thionamide is associated with various adverse effects, we re-evaluated the practical efficacy of potassium iodide (KI) therapy for Graves’ hyperthyroidism (GD). Methods: We administered KI (mainly 100 mg/day) to 324 untreated GD patients and added methimazole (MMI) only to those remaining thyrotoxic even at 200 mg/day. When the patient became hypothyroid, MMI, if taken was stopped, then levothyroxine (LT4) was added without reducing the KI dose. Radioactive iodine (RI) therapy or thyroidectomy was performed whenever required. We evaluated the early effects of KI at 2–4 weeks and followed patients for 2 years. Results: At 2 weeks, serum thyroid hormone levels decreased in all 324 patients. At 4 weeks, fT4, fT3, and both fT4 and fT3 levels became normal or low in 74.7%, 50.6%, and 50.6% of patients, respectively. In a cross-sectional survey over 2 years, GD was well-controlled with KI or KI + LT4 (KI-effective) in >50% of patients at all time points. Among 288 patients followed for 2 years, 42.7% remained ‘KI-effective’ throughout the 2 years (KI Group), 30.9% were well-controlled with additional MMI given for 1–24 months, and 26.4% were successfully treated with ablative therapy (mainly RI). Among ‘KI-effective’ patients at 4 weeks, 76.5% were classified into the KI Group. No patients experienced adverse effects from KI. Conclusion: KI therapy was useful in the treatment of GD. A sufficient dose of KI was effective in >50% of GD patients from 4 weeks to 2 years, and 42.7% (76.5% of ‘KI-effective’ patients at 4 weeks) remained ‘KI-effective’ throughout the 2 years.